EFFECT OF ALKALINE EXTRACTION ON THE FUNCTIONAL AND PHYSICOCHEMICAL PROPERTIES OF STARCH EXTRACTED FROM RICE, MILLET, AND OATS - Yaakob , Salwan. Ahmed; Nasser, Jassem. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
aimed to investigate the effect of alkaline extraction, using different concentration sodium hydroxide (NaOH) solution (0.6, 0.5, 0.4, 0.2)% on the physicochemical and functional properties and final yield of rice, millet and oat starch. The results showed that the yield of starch from rice flour ranged between (50 - 68.18)% and that the highest yield of starch was achieved using alkaline solution (NaOH) 0.4%, while for millet and oat the yield of starch ranged between (47.46 - 54)% and (48.3 - 62.66)% respectively, and the highest yield was recorded with (0.2)% (NaOH) for both crops. The percentage of amylose was high in the starch sample which was extracted using a low concentration of alkaline solution. The percentages of amylose were inversely related to functional properties (swelling capacity and solubility) which increased when the percentage of amylose in the obtained starch decreased. The highest values ​​of swelling capacity were (10.34)%, (8.11)% and (8.97)% for rice, millet , and oat starch samples.